2008
DOI: 10.1080/15421400801918179
|View full text |Cite
|
Sign up to set email alerts
|

Heat Treatments of Wood Fibers for Self-Bonding and Stabilized Fiberboards

Abstract: Heat treatment of wood fibers in a closed press for 4 and 8 minutes and pressed into fiberboards greatly reduces moisture regain and increases dimensional stability of the boards. Part of the hemicellulose sugars are lost during the steam treatment and furan intermediates were detected. Mannose, galactose, xylose, arabinose and rhamnose were partially lost during the steaming process. The steam treated boards have lower strength as compared to adhesive added boards but they do not fall apart when placed in wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…They observed that little furfurals were formed during the preparation of binderless fiberboards (Okuda et al 2006a). The discrepancy was probably the results of variations of detailed conditions, since the degradation of hemicelluloses has been reported to be highly dependent on moisture content, temperature, time of treatment and the composition of raw materials (Rowell and McSweeny 2008). Furthermore, Okuda et al (2006a) suggested that components decomposed from lignin during hot pressing could be extracted by methanol, indicating little contribution to self-bonding.…”
Section: Self-bonding Mechanism Of Binderless Fiberboardsmentioning
confidence: 94%
See 2 more Smart Citations
“…They observed that little furfurals were formed during the preparation of binderless fiberboards (Okuda et al 2006a). The discrepancy was probably the results of variations of detailed conditions, since the degradation of hemicelluloses has been reported to be highly dependent on moisture content, temperature, time of treatment and the composition of raw materials (Rowell and McSweeny 2008). Furthermore, Okuda et al (2006a) suggested that components decomposed from lignin during hot pressing could be extracted by methanol, indicating little contribution to self-bonding.…”
Section: Self-bonding Mechanism Of Binderless Fiberboardsmentioning
confidence: 94%
“…Several researchers have noticed that the content of free sugars generated from hemicelluloses during steam pretreatment of lignocellulosic materials experienced an increase to maximum and then decreased in the yield. This indicated potential reactions of these sugars to other products (Rowell and McSweeny 2008;Lawther et al 1996). Furthermore, furan monomers were found during the production of fiberboard (Cristescu and Karlsson 2013;Fahmy and Mobarak 2013;Tshabalala et al 2012).…”
Section: Self-bonding Mechanism Of Binderless Fiberboardsmentioning
confidence: 95%
See 1 more Smart Citation
“…The geometric increase of the world population demands that efforts be intensified to meet their material needs socially and economically. If in 1997, Rowell et al forecast that by the year 2000, twenty-five percent of China population would be their "middle class" and that the middle class would be more than the entire population of United State of America, then there is need to show more concern for the development of a new materials that can replace the conventional metals that are costly beyond the reach of the poor masses [1]. There is need for the replacement of metal and synthetic materials in order to reduce earth loads, prevent the use of the Petro-chemical byproducts and reduce their environmental impact and guide against the prediction that in less than fifty years (50), petroleum (fossil fuel) may go into extinction [2].…”
Section: Natural Fiber Reinforced Polymer Compositementioning
confidence: 99%
“…The moisture tolerance of hemicellulose based materials can be enhanced by lamination, 17 composite approach 18,19 and chemical modications. 23 High temperature heat-treatments result in reduced hydrophilicity mainly due to the increased crystallinity of cellulose, [24][25][26] cross-linking of lignin 27 or degradation of hemicelluloses; 28,29 however, treatments at high temperatures also result in decreased mechanical properties. 22 Heat-treatment is used for cellulosic materials, such as wood, to increase dimensional stability and durability by decreasing their moisture tolerance.…”
Section: Introductionmentioning
confidence: 99%